Virulence traits and expression of bstA, fliC and sopE2 in Salmonella Dublin strains isolated from humans and animals in Brazil - Vilela, Felipe Pinheiro; Gomes, Carolina Nogueira; Paziani, Mário Henrique; Braz, Vânia Santos [UNESP]; Rodrigues, Dália dos Prazeres; Costa, Renata Garcia; Tiba-Casas, Monique Ribeiro; Kress, Márcia Regina von Zeska; Falcão, Juliana Pfrimer; Campioni, Fábio (Elsevier, 2020)
Salmonella Dublin is a strongly cattle-adapted serovar that has also been responsible for severe invasive infections in humans. Although invasive infections by non-typhoid Salmonella have increased in developed and in developing countries, in sub-Saharan Africa these infections have been frequently related to Salmonella Typhimurium strains from Sequence Type (ST) 313 that harbor a possible virulence marker, the bstA gene, broadly detected in S. Dublin strains. The aims of this study were to verify the frequency of bstA by PCR in 113 Salmonella Dublin strains isolated from humans (83) and animals (30) in Brazil and the expression by RT-PCR of bstA, sopE2 and fliC in six strains isolated from humans (4) and animals (2). Moreover, the invasion capacity in Caco-2 human epithelial cells and U937 human macrophages, plus in vivo virulence analysis in Galleria mellonella and the motility were verified for 20 S. Dublin strains isolated from humans (15) and animals (5). All studied strains presented the bstA gene. The relative expression rates ranged from 0.1 to 2.3 fold change for bstA and from no expression to 16.6 fold change for sopE2, while no expression was detected for fliC. The invasion in Caco-2 cells ranged from 54.0 to 88.9% and in U937 cells from 72.9 to 98.1% in the 20 strains studied. In addition, 17 strains presented a highly virulent profile in the G. mellonella model and 15 strains presented a non-motile profile. In conclusion, the presence and expression of bstA in the S. Dublin strains studied suggested that this gene may influence in the invasive characteristic of this serovar. The low expression of sopE2 in strains from human invasive cases suggested that its expression may not be a limiting factor to the invasion of S. Dublin strains. The absence of fliC expression and the low motility rates observed suggest that the flagella absence may favor the host immune system evasion by S. Dublin and the establishment of infection. Moreover, the high mortality rates observed in vivo in Galleria mellonella reinforce the pathogenic potential of S. Dublin strains.
Keywords: Cell invasion; Galleria mellonella; RT-PCR; Salmonella Dublin; ST313